On a new operator from H∞ to the Bloch-type space on the unit ball - Stević, Stevo (Utilitas Mathematica, 2008)
We introduce a new operator denoted by Pψ g, which is a kind of the product of composition and integral operators on the unit ball B ⊂ ℂn. The boundedness and compactness of the operator from the space of bounded holomorphic functions H∞(B) to the Bloch-type space Bμ(B) or the little Bloch-type space Bμ0(B), are characterized.